Sex Differences in the Effects of a Kappa Opioid Receptor Antagonist in the Forced Swim Test - Laman-Maharg, Abigail; Williams, Alexia V.; Zufelt, Mikaela D.; Minie, Vanessa A.; Ramos-Maciel, Stephanie; Hao, Rebecca; Ordoñes Sanchez, Evelyn; Copeland, Tiffany; Silverman, Jill L.; Leigh, Angelina; Snyder, Rodney; Carroll, F. Ivy; et al. (Frontiers in Pharmacology, 2018)
There is growing evidence that kappa opioid receptor (KOR) antagonists could be a useful class of therapeutics for treating depression and anxiety. However, the overwhelming majority of preclinical investigations examining the behavioral effects of KOR antagonists have been in male rodents. Here, we examined the effects of the long-acting KOR antagonist nor-binaltophimine (norBNI) on immobility in the forced swim test in males and females of two different rodent species (C57Bl/6J and California mice). Consistent with previous reports, norBNI (10 mg/kg) decreased immobility in the forced swim test for male C57Bl/6J and California mice. Surprisingly, dose-response studies in female C57Bl/6J and California mice showed that norBNI did not reduce immobility. Pharmacokinetic analyses showed that metabolism and brain concentrations of norBNI were similar in male and female C57Bl/6J. In the nucleus accumbens of male but not female C57Bl/6J, norBNI increased phosphorylation of c-Jun N-terminal kinase (pJNK), a putative mechanism for norBNI action. However, no differences in pJNK were observed in male or female California mice. Together, these results suggest that immobility in the forced swim test is less dependent on endogenous KOR signaling in female rodents and highlight the importance of examining the effects of possible antidepressants in both males and females.